2012
DOI: 10.1038/aja.2012.24
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and prognostic factors for patients with bone metastases from prostate cancer

Abstract: To identify the clinical features and independent predictors of survival in patients with bone metastases from prostate cancer (PCa). We retrospectively analysed 115 PCa patients with bone metastases between 1997 and 2009. The overall survival rate after bone metastases was calculated using the Kaplan-Meier method. The prognostic factors were identified by univariate analysis using a log-rank test and by multivariate analysis using Cox proportional hazards regression models. The follow-up rate was 100%, the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…b Defined as brain, lung and liver metastases. the advantage of radiotherapy, 6 and the results were similar to those of another recent study. 15 However, in the current study, the older patients who received radiotherapy showed a lower survival rate when compared with the younger patients.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…b Defined as brain, lung and liver metastases. the advantage of radiotherapy, 6 and the results were similar to those of another recent study. 15 However, in the current study, the older patients who received radiotherapy showed a lower survival rate when compared with the younger patients.…”
Section: Discussionsupporting
confidence: 89%
“…9,12 In the current study, the median overall survival of patients with Gleason scores .8 was significantly shorter than that of the lower scoring patients, which is consistent with our previous study. 6 Cheville et al 13 and Yigitbasi et al 9 have also reported that among patients with bone metastases, the Gleason score of the primary prostate adenocarcinoma is strongly associated with patient outcome. Saeter et al 14 found that the survival of patients with soft tissue or non-regional lymph node metastasis was similar to that of patients presenting with skeletal metastasis only, but few studies have discussed the prognostic value of these factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10][11][12][13][14] However, the magnitude of the benefit provided by each factor has varied among studies, and the value of these factors in predicting overall survival (OS) for Chinese patients is still unclear. In the present study, we retrospectively analysed the data from 115 mCRPC patients treated with docetaxel to explore the prognostic factors of survival outcomes in Chinese patients.…”
Section: Introductionmentioning
confidence: 99%